The Effectiveness of Learning Mathematics Through Explicit Instruction Techniques at Santa Maria Private Junior High School Parmonangan Academic Year 2020/2021 - Yusniar Nova Tambunan (Jurnal Mantik, 2021)
The purpose of this research is to determine the effectiveness of learning mathematics through the Explicit Intruction technique with the help of Student Worksheets in teaching triangle material. The instruments used to determine the effectiveness of learning mathematics are the initial test, final test, and observation sheets as well as learning indicators in terms of 4 aspects, namely: student mastery level, student learning completeness, completeness of special learning objectives (TPK), student worksheets. The research subjects were all class VIII students of Santa Maria Parmonangan Private Junior High School, totaling 40 people and the research object was student learning outcomes and Student Worksheets (LKPD)The type of research used is descriptive research in the form of an essay. Before the material is taught, a preliminary test is given to determine the students' initial abilities and difficulties. The results of the initial tests show that students have low abilities. Of the 40 students, the percentage results obtained were 75% incomplete and 25% complete with an average of 46.65. Once applied Explicit intruction techniques with the help of Student Worksheets, carried out post-tests with the results of the percentage level of classical student learning completeness is 85% or an average of 69.4 in other words, classical student learning completeness has been achieved. Based on the TPK criteria, there are 4 TPKs. Of the 4 aspects of the effectiveness of mathematics learning, all of them are complete, namely: 80% Student Mastery Level, 85% Student Learning Completeness, 82.5% Completeness of Specific Learning Objectives, 77.5% Student Worksheets.) By applying explicit instruction techniques with the help of Sheets Students work in learning mathematics students on the material triangle student learning outcomes are increased and effective.